Towards solving perception based autonomous driving assistant system - Hossain, Md. Arafat; Rahman, Md. Sazidur; Islam, Md. Jisan Bin; Bhuiyan, Sazzad Alam (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.